Customer loyalty amongst GRADS member of Malaysia Airlines / Afini Salehuddin - Salehuddin, Afini (Faculty of Business and Management, 2006)
This exploratory research was carried out to obtain information about the values of benefits GRADS Programme and the perceived satisfaction of GRADS service quality from the GRADS members' point of view. The study was based on simple random sampling method using GRADS members as their sample. However the data was collected through face to face interview by using survey questionnaire in GRADS Counter Malaysia Airlines Building, Jalan Sultan Ismail, Kuala Lumpur and Road Show GRADS Programme at MATTA Fair, Putra World Trade Center, Kuala Lumpur. The overall findings of frequency from 132 respondents show that most valuable aspect of the GRADS Programme is the 50% rebate of domestic airfare for confirmed seat (90.91%) and the less valuable is Partner benefits(23.48%). Meanwhile 98.23% of the respondents are satisfied with the service quality of GRADS Counter, 90.91% of respondents are satisfied with the service quality of the application process, 97.88% of respondents are satisfied with the service quality of membership card, 96.72% of respondents satisfied with the service quality of benefits of GRADS Programme, 95.46% of respondents satisfied with the service quality of benefits 50% confirmed seat, 93.03% of respondents satisfied with the service quality of benefits 50% standby seat, and 95.30% of respondents satisfied with the Malaysia Airlines In-Flight service quality. On the other hand, the findings also indicated the factors that influenced the members to travel with Malaysia Airlines, season travel with Malaysia Airlines and purpose to travel with Malaysia Airlines. The study also indicated the major competitor of Malaysia Airlines and the factor of switching to other airlines. The research findings also indicated the statistical significant correlation between twenty three variables or attributes. The demographic variable of Years being GRADS Member, gender, age, race, nationality, level of study, monthly allowance, and RM 25 as annual fees correlate with GRADS Programme attributes, factors to travel with Malaysia Airlines, and perceived satisfaction of GRADS Programme attributes. With identifying the problems and shortcoming of valuable benefits and perceived satisfaction of GRADS Programme, it can provide general guideline and ideas to improve the programme as well as to enhance customer loyalty with Malaysia Airlines in future. Recommendations and suggestion on how to improve the value of benefits GRADS Programme and perceived satisfaction of GRADS Programme have been identified. Furthermore implications for future research is also being discussed for achieving further involvement in fields of benefits and perceived satisfaction of GRADS Programme.